Food Provision Indicators of Renuka Forest Division, Himachal Pradesh, Western Himalaya - Yadav, Vinod Kumar; Yadav, Shilpa; Rawat, Laxmi; Adhikari, B. S. (Indian Forester, 2021)
Forest Ecosystem contribute to food and shelter to local people in various ways. Trees of forest ecosystem provide variety of foods including fruits, vegetables, nuts, seeds etc. It also supports the provision of fodder for meat and dairy animals. There are complexities in quantifying the relative benefits and costs of forest ecosystem in food provision. These complexities mean that the roles of tree based systems are often not well understood. In the present study, food provision which is extracted from the forest by the local households of Renuka Forest Division and their extraction proportion was studied. The extraction proportion can be used as indicators for further quantification of extracted resources and in various forest conservation practices.